ANALYSIS OF AN HLA-B MOSAICISM OBSERVED IN APHERESIS DONOR - Ota, Satoshi; Tamaki, Keiko; Seshimo, Hideyuki; Nomura, Setsuo; Komatsu, Yumi; Yamazaki, Yuichiro; Saito, Satoshi (Journal of the Japan Society of Blood Transfusion, 2005)
We encountered an apheresis donor with a suspected case of mosaicism. The donor, K. A., was a 46-year-old Japanese female registered as an HLA-compatible platelet concentrate (HLA-PCs) donor. In her HLA serological typing for HLA-PCs donor registration, three antigens, HLA-B55, -B61 and -B62, were assigned in the HLA-B locus. She was not a twin and had never undergone transfusion or transplantation. Flow cytometric analysis using platelets and lymphocytes indicated that HLA-B55, -B61 and -B62 antigens were simultaneously expressed on the surface of platelets and lymphocytes. HLA-B allele typing with the polymerase chain reaction restriction fragment length polymorphism technique using genomic DNA from peripheral blood and nails as a somatic sample was carried out to establish HLA-B mosaicism. Three alleles, HLA-B*5502, -B*4002 and B*1501, were assigned in both exon 2 and exon 3. HLA-B mosaicism was observed in both her peripheral blood and nails. The HLA-B*4002 and -B*1501 alleles were inherited by her son, who carried three HLA-B alleles, HLA-B*4002, -B*1501 and -B*4001. No other sign of chimerism or mosaicism was observed in other HLA loci antigens or red cell antigens. These results suggest that this donor has a chimeric allele consisting of a mixture of the nucleotide sequences of HLA-B*4002 and -B*1501 alleles.